2007
DOI: 10.1523/jneurosci.0095-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spike Timing Amplifies the Effect of Electric Fields on Neurons: Implications for Endogenous Field Effects

Abstract: Despite compelling phenomenological evidence that small electric fields (Ͻ5 mV/mm) can affect brain function, a quantitative and experimentally verified theory is currently lacking. Here we demonstrate a novel mechanism by which the nonlinear properties of single neurons "amplify" the effect of small electric fields: when concurrent to suprathreshold synaptic input, small electric fields can have significant effects on spike timing. For low-frequency fields, our theory predicts a linear dependency of spike tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
229
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(251 citation statements)
references
References 55 publications
(63 reference statements)
15
229
0
Order By: Relevance
“…Extracellular recordings of local field potentials (LFPs) directly from the cortex reveal bursts of oscillatory activity. These might modulate stimulus-related activity, either directly (by providing additional synaptic inputs) or indirectly (by generating gradients in the extracellular potential 58 ), and thus might cause the apparent imprecision of cortical responses described above.…”
Section: The Contribution Of Cortical Oscillations To Precisionmentioning
confidence: 99%
“…Extracellular recordings of local field potentials (LFPs) directly from the cortex reveal bursts of oscillatory activity. These might modulate stimulus-related activity, either directly (by providing additional synaptic inputs) or indirectly (by generating gradients in the extracellular potential 58 ), and thus might cause the apparent imprecision of cortical responses described above.…”
Section: The Contribution Of Cortical Oscillations To Precisionmentioning
confidence: 99%
“…Recently several studies have reported that endogenous electric fields provide an effective (and maybe indispensable) mechanism for a rapid orchestration of neocortical spatiotemporal synchronization patterns (e.g., Anastassiou et al, , 2011Fröhlich and MecCormick, 2010;Marshall et al, 2006;Ozen et al, 2010;Radman and Nicholson, 2007;Weiss and Paulsen, 2010). Although the magnitude of local fields is considerably lower than the typical threshold potential of a neuron Fröhlich and MecCormick, 2010) they still may modulate spike timing of single neurons via ephaptic coupling (Radman and Nicholson, 2007) as well as the collective neuronal dynamics of entire neuronal populations (Fröhlich and MecCormick, 2010;Weiss and Paulsen, 2010).…”
Section: Volume Conduction and Choice Of Referencementioning
confidence: 99%
“…Although the magnitude of local fields is considerably lower than the typical threshold potential of a neuron Fröhlich and MecCormick, 2010) they still may modulate spike timing of single neurons via ephaptic coupling (Radman and Nicholson, 2007) as well as the collective neuronal dynamics of entire neuronal populations (Fröhlich and MecCormick, 2010;Weiss and Paulsen, 2010). Endogenous local fields modulate neuronal membrane potentials on a subthreshold level (Fröh-lich and MecCormick, 2010;Ozen et al, 2010;Weiss and Paulsen, 2010) and thereby influence network activity.…”
Section: Volume Conduction and Choice Of Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Radman, Su, An, Parra, and Bikson (2007) investigated the effect of Local Field Potentials (LFPs) on neural spikes and found that hyperpolarizing LFP delayed action potential while depolarizing LFP advanced it. In our model, an oscillatory signal representing LFP modulates the phase of the neural spikes.…”
Section: Introductionmentioning
confidence: 99%